Escola de samba na mídia : a cobertura do carnaval de Porto Alegre nos jornais Correio do Povo e Zero Hora entre 2001 e 2005 - Dutra, Édson Luís (2024)
This work aims to understand how the print media covered the Porto Alegre carnival from 2001 to 2005, through content and discourse analyzes of the carnival coverage of the newspapers Correio do Povo and Zero Hora. As a bibliographical route, studies were consulted that address the history of carnival, the samba school and the relationship between culture and communication, based on the concepts of Folkcommunication, cultural journalism and carnival journalism. The results obtained in this research show that the newspaper Correio do Povo used communication tools that enabled in-depth analysis of the information produced, as well as the production of a propositional discourse on the samba school parades, in comparison to the newspaper Zero Hora. This research opens space for new investigations into the role of the media in covering and promoting popular culture, especially samba schools